EKOLOGI MAKAN IKAN GLYPTOTHORAX MAJOR (BLGR) (BAGARIDAE, SILURIFORMES) DI SUNGAI ALAS, ACEH TENGGARA - RACHMATIKA, IKE; WIRJOATMODJO, SOETIKNO (BERITA BIOLOGI, 1988)
IKE RACHMATIKA & SOETIKNO WIRJOATMODJO.1988.Feeding ecology of Glyptothorax major Blgr) (Bagaridae, Silurifoimes) in the Ala River,South East Aceh. Berita Biologi. 3(8): 396 399.A study on the feeding ecology of Glyptothorax major (Blgr) was conducted in the Alas River South East Aceh, Sumatra during early dry season, January 1983.Index of Preponderance analysis showed that this species is a benthic-insect feeder It was found that the food habit of immature and mature fish is slightly different.The mature fish's food habit is more varied than the immature's. Based on the concept of the "availability factor"of prey species,a tendency was also found that the mature fish is a more opportunistic of using food resources than the immature's.The supposed mechanisme of this difference and its relation with condition factor values is discussed.